Capacity development in decentralized planning of local government in Cambodia : a case study of Banteay Meanchey Province - Mao Sotheary; Soparth Pongquan; Ahmad, Mokbul Morshed; Kyoko Kusakabe; Government of Norway (NORAD) (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
The research assesses the capacity level of local government in performing the decentralized planning in rural development in Banteay Meanchey province in Cambodia. The specific objectives of this research were to examine a capacity building program for local government; assess the capacity level of the local government in their performance of CDPP; obtain feedback of the local government on the capacity building program and their performance on the CDPP; identify factors influencing the capacity level of the local government on the CDPP; and to give recommendations to strengthen the capacity development program of the local government and suggest policy implications on the decentralized rural development. This study was focused on the local government at a commune level. The capacity building program undertaken in this research was in common throughout the country provided by the Mol and the Seila Program. The main actors of the local government observed in this research were primarily comprised of CCs and PBCs. The CDPP included in this research consisted of 11 steps defined by Prakas of the Mol and also incorporated the implementation and monitoring and evaluation steps. The research was conducted in two communes namely Banteay Neang and Batrang, in Banteay Meanchey province. A set of standardized questionnaire was utilized to collect data from CCs and PBCs. Other tools were used comprising of field observation, key informants interview, group discussion and PRA. The research used both quantitative and qualitative analysis. The findings of this research showed that the capacity of the local government was enhanced rather effectively through several activities in the capacity building program covering training, workshop, on-the-job training and monthly bulletin. The CCs and PBCs found those activities appropriate, useful, accessible, being very satisfied and having a high understanding level. Despite of being capable in many tasks of the CDPP, the local government was incapable in certain steps of the CDPP in comparison between the two communes. Banteay Neang had a relatively better in drafting a local map, DIW and organizing meetings while Batrang had better performance in report preparation, good work coordination among the CCs and in resource mobilization. Factors influencing to the capacity level were on-the-job training, group discussion, technical support from PFT, DFT, transportation means, supplementary income, training per diem, understanding level on training topics, frequency of attendance in the training program and on-the-job training, and frequency of the receipt of a monthly bulletin per annum. Certain limitations were found in the CDPP performance of the local government including data analysis, bidding, contracting, monitoring and evaluation and report writing. Their weaknesses were also found in other development aspects consisting of communication, critical thinking and analytical skills, data updating, record keeping, work disciplinary, resource mobilization, networking and team work building. Certain recommendations were made in this research to strengthen the capacity level of the local government capacity level in the CDPP performance. Specific suggestions were also made to improve the CDPP so that the local capacity could be effectively enhanced as a consequence. Policy implications on the decentralization for local government were outlined in perspective on the local capacity development to make the policy become more effective in future
A thesis proposal submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 2006
Keywords: Local government -- Cambodia -- Banteay Meanchey; Decentralization in government -- Cambodia -- Banteay Meanchey